A survey of value prediction techniques for leveraging value locality. (11th September 2017) - Mittal, Sparsh
Summary: Value locality (VL) refers to recurrence of values in a memory structure, and value prediction (VP) refers to predicting VL and leveraging it for diverse optimizations. VP holds the promise of exceeding true‐data dependencies and provide performance and bandwidth advantages in both single‐ and multi‐threaded applications. Fully exploiting the potential of VL, however, requires addressing several challenges, such as achieving high accuracy and coverage, reducing hardware and latency overheads, etc. In this paper, we present a survey of techniques for leveraging value locality. We categorize the research works based on key parameters to provide insights and highlight similarities and differences. This paper is expected to be useful for researchers, processor architects, and chip‐designers.